IFPRI Policy Seminar: Innovations in Measuring Women's Empowerment -- FTF Results Framework - Hogue, Emily; Quisumbing, Agnes R.; Alkire, Sabina; Hogue, Emily (2012)
Policy Seminar Presentation with Emily Hogue, Agnes Quisumbing and Sabina Alkire on March 21, 2012. Slide courtesy of Emily Hogue.